1984
DOI: 10.18785/negs.0701.02
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Abundance, and Biology of the Blacknose Shark, Carcharhinus acronotus, in North Carolina

Abstract: The biology of the blacknose shark, Carcharhinus acronotus, is presented for specimens captured by longlining off Shackleford Banks, North Carolina between 1973 and 1982. This entails comments on the number, seasonality, catch rate, color, age, growth, size, maturity, meristics, morphology, reproduction and parasites. C. acronotus frequents North Carolina coastal waters from May to October. Males dominate catches through July; females from August to early fall catches. Catches varied among years,and were proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
26
2

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 4 publications
5
26
2
Order By: Relevance
“…This overestimate has been noted for several carcharhinid sharks (Casey et al 1985, Parsons 198.5, Branstetter & McEachran 1986). The K value (0.076) was similar to values derived for Carcharhinus plumbeus (Casey et al 1985) and Sphyrna lewini (Branstetter 1987a), but was much lower than values estimated for the more rapidly growing C. acronotus (Schwartz 1983b), C. fafciformis (Branstetter 1987a), C. fimbatus, and C. brevipinna (Branstetter 1987~). Although Compagno (1984) listed the maximum length of C. leucas to be near 340 cm, only one specimen (316 cm: Sadowsky 1967) has been reported to exceed 300 cm (see Garrick 1982 for review).…”
Section: Centrum Analysissupporting
confidence: 72%
“…This overestimate has been noted for several carcharhinid sharks (Casey et al 1985, Parsons 198.5, Branstetter & McEachran 1986). The K value (0.076) was similar to values derived for Carcharhinus plumbeus (Casey et al 1985) and Sphyrna lewini (Branstetter 1987a), but was much lower than values estimated for the more rapidly growing C. acronotus (Schwartz 1983b), C. fafciformis (Branstetter 1987a), C. fimbatus, and C. brevipinna (Branstetter 1987~). Although Compagno (1984) listed the maximum length of C. leucas to be near 340 cm, only one specimen (316 cm: Sadowsky 1967) has been reported to exceed 300 cm (see Garrick 1982 for review).…”
Section: Centrum Analysissupporting
confidence: 72%
“…) and in the Gulf of Mexico (Sulikowski et al, 2007). The progressive increase in embryos TL over the months suggests a 9 month gestation period, which is similar to that described by Hazin et al (2002) and Schwartz (1984), respectively, 8 and 9 months, and lower to values presented by Dodrill (1977) and Driggers et al (2004), which were between 11 and 12 months (both studies were carried out off Florida, USA). This divergence may be related to different temperature gradients in the study locations; it is possible that warmer waters at latitudes closer to the equator accelerate reproductive processes (fecundity, maturation, etc.)…”
supporting
confidence: 85%
“…The size at first sexual maturity found for females (around 105.0 cm TL) is smaller than that described by Branstetter (1981;113.0 cm TL), but larger than 96.4 cm described by Driggers et al (2004). The size at first maturity for males (here estimated at around 105.0 cm) was slightly smaller than that described by Schwartz (1984;110.0 cm TL), but closer to the 104.0 cm described by Hazin et al (2002) Hazin et al (2002 suggest that birth size for blacknose shark is approximately 45.0 cm TL. In the present study, 2 females were observed at term with mean embryo sizes of 50.0 cm and 63.2 cm TL, suggesting that the 45.0 cm birth size may have been underestimated.…”
contrasting
confidence: 59%
“…The skin of this specimen was preserved, but has apparently been lost (Compagno, 2001) , but specimens from much shallower water reported by Kerstetter & Taylor (2008) and Castro (2011) 853 (Bigelow & Schroeder, 1948) or 2200 mm cannot be assigned to concrete specimens. A specimen of 2400 mm reported by Fowler (1945) was not this species (Schwartz, 1984) 72 Lessa et al (1999) is much deeper than other references. Specimens from the NEA and SEA might belong to a distinct species based on molecular data so that one of the species currently placed in the synonymy of C. brachyurus might need to be resurrected (Naylor et al, 2012a) 855 (Garrick, 1982;White & Weigmann, 2014) 856 White, 2014, pers.…”
Section: Jordan 1898mentioning
confidence: 81%